NEW ENVIRONMENTALLY BENIGN LEATHER TECHNOLOGY: COMBINATION TANNING USING VEGETABLE TANNIN, NAPHTHOL AND OXAZOLIDINE - Ono Suparno, Anthony D. Covington dan Christine S. Evans (Jurnal Teknologi Industri Pertanian, 2008)
ABSTRACTLeather tanning is a process of converting of skin or hide protein into leather with adequate strength properties, resistance to various biological and physical agents, and capable of being used for a wide range of purposes.  Leather tanning reactions between collagen-vegetable tannin-oxazolidine and collagen-dihydroxynaphthalenes (DHNs)-oxazolidine have been investigated using hide powder and sheepskin pickled pelt. This investigation showed that some DHNs have a tanning effect on collagen.  The measurement of combined and cross-linked vegetable tannin and DHNs on collagen showed that 20-50% vegetable tannin, 1,6- and 2,6-DHNs were fixed through covalent bonding.  Shrinkage temperature of the leather changed little after the non combined vegetable tannin and DHNs had been removed from the leather, indicating that the high stability of the combination tanned leather comes from the covalent bonding formed between vegetable tannage or DHNs and collagen through oxazolidine. Covalently bound tannin on collagen was more stable and could not be extracted by lyotropic agents. Keywords: tanning, leather, hydrothermal stability, vegetable tannage, dihydroxynaphthalenes, oxazolidine.